Analisis Faktor–Faktor yang Memengaruhi Keterlambatan Daya Serap Anggaran (Studi Empiris Pada SKPD Pemprov NTB) - Rifai, Ahmad; Inapty, Biana Adha; Pancawati M., Rr Sri (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 11 No 1 (2016)DO - 10.24843/JIAB.2016.v11.i01.p01, 2016)
The purpose of this study to determine whether the planning, regulation, coordination, implementation, decentralization and human resources are all factors that influence delays in budget absorption. This type of research is a survey research with purposive sampling technique that personnel involved in the budgeting process and apparatus that are involved in the process of administration. The analysis technique used is multiple linear regression analysis to analyze the variables influence the planning, regulation, coordination, implementation, decentralization and human resources in the budget absorption. Results of the study found that the planning, regulation, implementation, decentralization, coordination and human resources do not affect the absorption delay budget. Future studies should broaden the scope of the sample and fix the indicator variables are used primarily for budgeting, planning-related issues. Keywords: Absorption budget, planning, regulation, coordination, implementation
Keywords: Absorption budget, Planning, Regulation, Coordination, Implementation